2013
DOI: 10.1186/1471-244x-13-106
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in first episode psychosis: a one-year follow-up study

Abstract: BackgroundDepressive symptoms are common in patients with first episode psychosis (FEP) and have serious consequences for them. The main aims of this study were to examine the course of depression in FEP patients and explore whether any patient characteristics at baseline predicts depressive symptoms after one year.MethodA total of 198 FEP patients with schizophrenia spectrum disorders were assessed for depressive symptoms with Calgary Depression Scale for Schizophrenia (CDSS) at baseline and 127 were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
22
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 40 publications
11
22
2
2
Order By: Relevance
“…Poor premorbid social functioning may be such a vulnerability factor in patients with psychosis. This is also in line with a recently published study which found that poor premorbid social functioning in childhood, DUP and PANSS depressive component predicted depressive symptoms at 12 months of follow up …”
Section: Discussionsupporting
confidence: 93%
“…Poor premorbid social functioning may be such a vulnerability factor in patients with psychosis. This is also in line with a recently published study which found that poor premorbid social functioning in childhood, DUP and PANSS depressive component predicted depressive symptoms at 12 months of follow up …”
Section: Discussionsupporting
confidence: 93%
“…There were few clinical variables linked with this outcome at one year but at baseline perceived support is linked to depression which is similar to other research (Sundermann et al, 2014) but opposes the finding from a similar study that depression is not linked with social support satisfaction (Malla et al, 2004). We found similar levels of depression in our cohort when compared to similar first-episode psychosis cohorts indicating that greater levels of depression do not explain this finding (Malla et al, 2004, Sönmez et al, 2013. At one year, depression was not linked with perceived social support although an overall reduction in clinically significant depression from 20% to 3% in the entire sample may partially explain this finding despite a greater need to consider depressive symptoms as a treatment target during the acute phase of treatment (Renwick et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…Alternatively, the finding may reflect that a high social disability leads to an increase in depressive symptoms. Nevertheless, the significance of depression reflects the high level of depression in first episode psychosis, being present in 50% at treatment initiation [35] and 35% at one year follow-up [36]. The only disability domain that was associated with negative symptoms was "Understanding and communicating" which largely represents cognition, which is in line with studies finding a close relationship between negative symptoms and cognitive impairment [37].…”
Section: Gaf-f Csupporting
confidence: 61%